The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1103/physrevd.99.043522
|View full text |Cite
|
Sign up to set email alerts
|

General theory of cosmological perturbations in open and closed universes from the Horndeski action

Abstract: Our Universe is nearly spatially flat, but this does not mean that it is exactly spatially flat. In this paper we derive general quadratic actions for cosmological perturbations in non-flat models from the Horndeski theory. This allows us to study how the spatial curvature influences the behavior of cosmological perturbations in the early universe described by some general scalar-tensor theory. We show that a tiny spatial curvature at the onset of inflation is unlikely to yield large (or O(1)) effects on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 79 publications
(99 reference statements)
1
14
0
Order By: Relevance
“…For ξ = O(1) we have γ − 1 = O(1), which clearly contradicts the solar-system experiments [221]. Now we add a Galileon-like cubic interaction to (134):…”
Section: A Vainshtein Primermentioning
confidence: 79%
“…For ξ = O(1) we have γ − 1 = O(1), which clearly contradicts the solar-system experiments [221]. Now we add a Galileon-like cubic interaction to (134):…”
Section: A Vainshtein Primermentioning
confidence: 79%
“…Recently, striking studies have been conducted. A quite wide class of singularity-free cosmological solutions in Friedmann-Lemaître-Robertson-Walker (FLRW) spacetime is proved to be unstable [16][17][18][19]. Since the no-go theorem is established based on the Horndeski theory, in other words, the most generalized scalartensor theory whose equation of motion is up to second order [20], one may consider it is difficult to find stable cosmological solutions without a singularity.…”
Section: Introductionmentioning
confidence: 99%
“…Not only the time crystal Universe but any bouncing Universe in Horndeski theory tends to suffer from the stability issue [27]. In case of the Universe with a spatial curvature, the stability is studied [28] and found that the tensor perturbation is stable if and only if the following inequalities are satisfied:…”
Section: Summary and Discussionmentioning
confidence: 99%
“…These analyses show the presence of gradient instability [25,26] and finally no-go theorem for stable bouncing cosmology in Horndeski theory was found for the spatially flat Universe [27]. However, it was shown that no-go theorem does not hold when the spatial curvature is included [28]. Therefore, we should consider Horndeski theory in the presence of a spatial curvature in order to have a bouncing Universe [29].…”
Section: Introductionmentioning
confidence: 96%